2020
DOI: 10.1002/celc.202001035
|View full text |Cite
|
Sign up to set email alerts
|

Azobenzene‐Based Low‐Potential Anolyte for Nonaqueous Organic Redox Flow Batteries

Abstract: Redox flow batteries (RFBs) using organic materials in organic solvents are particularly promising because of the diversity of organic materials and the wide redox‐innocent window of organic solvents, yet the further development of this type of RFB has been hindered by the lack of suitable anolyte materials with high potentials, solubility, and stability. Herein, we examine the physical and electrochemical properties of azobenzene (AzoPh) compounds and investigate their degradation mechanism in nonaqueous orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 71 publications
1
17
0
Order By: Relevance
“…Wang et al revealed that this behavior was due to the fact that one-electron reduction accompanied by protonation in the organic solvent assisted degradation into aniline or dimerization. [55] As mentioned above, azo molecules act as highperformance anolytes because of their high solubility, fast redox reaction, and the coupling between the redox reaction, which high capacity and voltage increase (Table 5).…”
Section: Minireviewsmentioning
confidence: 99%
“…Wang et al revealed that this behavior was due to the fact that one-electron reduction accompanied by protonation in the organic solvent assisted degradation into aniline or dimerization. [55] As mentioned above, azo molecules act as highperformance anolytes because of their high solubility, fast redox reaction, and the coupling between the redox reaction, which high capacity and voltage increase (Table 5).…”
Section: Minireviewsmentioning
confidence: 99%
“…We next changed the solvent to DMF on the basis of its comparable dielectric constant (ε = 38 compared to 39 for MeCN) and literature reports showing the improved redox stability of low-potential anolytes in this medium. ,, As shown in Figure (red), the redox potentials of 1 and 2 in DMF are lower than those in MeCN (−2.91 and −2.71 V vs Fc/Fc + , respectively). Furthermore, the peak height ratios ( i pc / i pa values) are closer to 1, at 0.87 and 0.91, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Wang et al. revealed that this behavior was due to the fact that one‐electron reduction accompanied by protonation in the organic solvent assisted degradation into aniline or dimerization [55] …”
Section: Anolytes For Rfbsmentioning
confidence: 99%
“…Wang et al revealed that this behavior was due to the fact that one-electron reduction accompanied by protonation in the organic solvent assisted degradation into aniline or dimerization. [55] As mentioned above, azo molecules act as highperformance anolytes because their high solubility, fast redox reaction, and the coupling between the redox reaction, which provides high capacity and voltage increase (Table 5).…”
Section: Kurzaufsätzementioning
confidence: 99%